Reformation of the Scientific and Technical Sphere in the Russian Federation in the "Transition Period": Plans and Reality in 1990s - Bodrova, Elena Vladimirovna; Kalinov, Vyacheslav Viktorovich (Journal of History Culture and Art Research, 2017)
The paper analyzes the situation that has been developed after the collapse of the former USSR in the scientific and technical complex of the Russian Federation, which, according to the authors, developed from a crisis situation to a catastrophic one. The conclusion is drawn that its degradation was caused not only by the general paralysis of the socioeconomic sphere, and also by the lack of a conceptually elaborated state industrial, scientific and technical and innovation policy, by the weakness of the legal framework and the erroneous priorities chosen at that time by the reformers. In general, the state scientific and technical policy in the period under review was characterized by inconsistency and persistently unrealized plans.